GenBank - Sayers, Eric W; Cavanaugh, Mark; Clark, Karen; Ostell, James; Pruitt, Kim D; Karsch-Mizrachi, Ilene (Nucleic acids research, 2020)
Abstract GenBank® (www.ncbi.nlm.nih.gov/genbank/) is a comprehensive, public database that contains over 6.25 trillion base pairs from over 1.6 billion nucleotide sequences for 450 000 formally described species. Daily data exchange with the European Nucleotide Archive (ENA) and the DNA Data Bank of Japan (DDBJ) ensures worldwide coverage. Recent updates include a new version of Genome Workbench that supports GenBank submissions, new submission wizards for viral genomes, enhancements to BankIt and improved handling of taxonomy for sequences from pathogens.